THE SAKRAL: INOVASI SALE BERBAHAN JAMBU KRISTAL SEBAGAI PELUANG USAHA BERBASIS POTENSI LOKAL DI DESA PAMIJAHAN KABUPATEN BOGOR - Hasanah, Tita; Lestari, Fitri; Sakilah, Ilah; Maulana, Rizki; Kusumaningrum, Ria (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2023)
One type of guava that is widely grown by the people of Pamijahan Village, Bogor Regency, is Crystal Guava. In general, this guava fruit is consumed by eating it directly, asinan, juice, petisan, and fruit salad. There are no other interesting processed variations that can become business opportunities for the community. Therefore, one of the Kuliah Kerja Nyata (community service) programs of the Sahid Bogor Islamic Institute group 01 is to examine innovations made from crystal guava as a business opportunity for the community. The method is Service Learning. The steps taken are conducting trials on several types of guava processing, conducting outreach to stake holders, conducting guava processing training, and evaluating activities. The results of this activity program resulted in an innovation, namely the Sale Kristal which was named “The Sakral”